2021
DOI: 10.5334/joc.186
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the Evidence for Asymmetrical Switch Costs and Reversed Language Dominance Effects – A Meta-Analysis

Abstract: Two seemingly counterintuitive phenomena – asymmetrical language switch costs and the reversed language dominance effect – prove to be particularly controversial in the literature on language control. Asymmetrical language switch costs refer to the larger costs for switching into the dominant language compared to switching into the less dominant language, both relative to staying in either one language. The reversed language dominance effect refers to longer reaction times when in the more dominant of the two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 107 publications
4
27
0
Order By: Relevance
“…In addition, we observed switch costs as expected: In a switch trial, it is harder to activate the correct language, as it had been inhibited on the previous trial. Interestingly, we did not find any evidence for asymmetrical switch costs (i.e., more pronounced switch costs for L1 than L2) across experiments; while asymmetrical switch costs have been reported under some circumstances, recent evidence indicates that they may not be as robust as previously thought ( Gade et al, 2021 )—our data are consistent with that conclusion. Overall, these results suggest that implementing a predictable sequence did not fundamentally change how pictures were named.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, we observed switch costs as expected: In a switch trial, it is harder to activate the correct language, as it had been inhibited on the previous trial. Interestingly, we did not find any evidence for asymmetrical switch costs (i.e., more pronounced switch costs for L1 than L2) across experiments; while asymmetrical switch costs have been reported under some circumstances, recent evidence indicates that they may not be as robust as previously thought ( Gade et al, 2021 )—our data are consistent with that conclusion. Overall, these results suggest that implementing a predictable sequence did not fundamentally change how pictures were named.…”
Section: Discussionsupporting
confidence: 87%
“…in multilinguals). These asymmetric switch costs are sometimes observed (e.g., Experiment 1 by Costa & Santesteban, 2004;Meuter & Allport, 1999; though not always, see Experiments 2-4 by Costa & Santesteban, 2004;Declerck et al, 2012;Gade et al, 2021;Slevc et al, 2016) and are consistent with the ICM predictions.…”
Section: The Role Of Proactive Language Control In Bilingual Language...supporting
confidence: 81%
See 1 more Smart Citation
“… This article details a correction to: Gade, M., Declerck, M., Philipp, A. M., Rey-Mermet, A., & Koch, I. ( 2021 ). Assessing the Evidence for Asymmetrical Switch Costs and Reversed Language Dominance Effects – A Meta-Analysis.…”
mentioning
confidence: 95%
“…Specifically, many studies reported that switching to a dominant (typically in the sense of better trained) task results in larger switch costs than switching to the less dominant task (e.g., Allport et al, 1994 ; Allport & Wylie, 1999 ; de Jong, 1995 ; Monsell et al, 2000 ; Yeung & Monsell, 2003 ). For example, Meuter and Allport ( 1999 ) observed asymmetric switch costs in the context of language switching: When bilingual participants switched between digit naming in their (better trained) first language versus their second language, they responded more slowly in their second (vs. first) language in repetition trials, but faster in their second (vs. first) language in switch trials (see, e.g., Declerck & Philipp, 2015 , for a review; but see Gade et al, 2021 , for limits regarding a generalization of these effects).…”
Section: Introductionmentioning
confidence: 99%